Micro Entrepreneurs' Intention Towards Islamic Working Capital Financing: Pecking Order Theory Perspective - Heryanto, Hanifa Khoirunnisaa; Muflih, Muhammad; Marwansyah, Marwansyah (Jurnal Ilmiah Ekonomi Islam, 2024)
The banking world has a significant role in helping MSMEs to increase Indonesia's economic growth. One solution offered is by providing working capital financing based on Murabahah and Ijarah contracts. This research aims to examine Maqasid al-Sharia, risk perception, margin cost perception, and prospects as the determinants of micro entrepreneurs' intention to increase working capital financing in Islamic banks. The research method used a quantitative approach for data collection and analysis. The sampling technique used purposive sampling for micro-entrepreneurs who know the existence of Islamic banks. The data was collected by conducting both online and offline surveys. A final sample of 286 respondents was analyzed using SmartPLS software to predict relationships between latent variables. Based on the data processing results, the perception of margin costs and prospects has a significant impact. In contrast, Maqasid al-Sharia and risk perception do not influence the micro entrepreneurs’ intention to use Islamic working capital financing.